Seedling Morphology and Phytomass of Bauhinia retusa Buch.-Ham. Ex Roxb.-A Promising Species for Reforestation of Limestone Spoils in W. Himalaya - Gupta, R. K. (Indian Forester, 1978)
Observations on the seedling morphology and phytomass of Bauhinia retusa have been recorded ever the period of six months. The species is promising for reforestation of limestone quarry spoils and degraded community lands in the outer hill ranges of Mussoorie and other analogous phyto-climatic regions.